Surgical outcome of scoliosis in Marfan syndrome: a case series report - komang agung irianto; Gestana R Wardana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Scoliosis in marfan syndrome (MFS) manifests on 60% patients. Moreover, the scoliosisnoticeable in earlier age is more progressive, refracted, and rigid compared to idiopathicadult scoliosis. The surgical correction provides notorious higher perioperative risk,whereas conservative treatment using brace is not effective to prevent progressivityof the scoliosis. In this a case report, we reported the surgical outcome of MFS scoliaispatients with MFS who operated using posterior fusion instrumentation by mean of thequality of life SF-36 questioner. This was a retrospective case series involving five MFSscoliosis patients who underwent posterior fusion instrumentation with initial Cobb angleof 87.417.57o and initial kyphotic angle of 32.8 ± 14.52o. Clinical, radiological andquality of life of the patients based on SF-36 questionnaire were evaluated within 6-36months follow up. Post-operative showed the Cobb angle become 46.2 ± 16.3o and thekyphotic angle become 21.6 ± 9.94o. No intraoperative or post-operative complicationswere observed. After 6-36 months follow up, the Cobb angle became 45.2 ± 17.48oand the kyphotic angle became 21.6 ± 9.94o. In addition, all patients had physical andmental health scored similar to 2 years post-surgery scoliosis scoring according to SF-36 orthopedic scoring guidelines. I conclusion, the surgical outcome of posterior fusioninstrumentation in MFS scoliosis showed good correction of Cobb angle and Kyphoticangle. The quality of life of the patients based on physical and mental health questionnaireis satisfactory.